An Immune-Related Prognostic Signature Predicts Overall Survival in Stomach Adenocarcinomas - Zhou, Kangjie; Hu, Nan; Hong, Yidong; Wu, Xueyu; Zhang, Jingzhou; Lai, Huan; Zhang, Yang; Wu, Fenglei (Frontiers in Genetics, 2022)
This study aimed to explore an immune response-related gene signature to predict the clinical prognosis and tumor immunity of Stomach adenocarcinomas (STAD). Based on the expression and clinical data of STAD in TCGA database, the immune cells infiltration status was evaluated using CIBERSORT and ESTIMATE methods. Samples were grouped into “hot” and “cold” tumors based on immune cells infiltration status and consensus clustering. The infiltration abundance of activated memory CD4 T cells and CD8 T cells had significant effect to overall survival of STAD patients. Among of the three clusters, Cluster 2 had higher immune-score and significant higher abundance of CD8 T cells and activated memory CD4 T cells were assigned as hot tumor, while Cluster 1 and 3 assigned as cold tumor. DEGs between hot and cold tumors were mainly enriched in immune-related biological processes and pathways. Total of 13 DEGs were related to the overall survival (OS). After Univariate and multivariable Cox regression analysis, three signature genes (PEG10, DKK1 and RGS1) were identified to establish prognostic model. Patients with high-risk score was associated with worse survival, and the risk score had independent prognostic value. Based on TIMER online tool, the infiltration levels of six immune cell types showed significant differences among different copy number status of PEG10, DKK1 and RGS1. In this study, an immune-related prognostic model containing three genes was established to predict survival for STAD patients.